Characteristics of Silicone Oil Emulsification After Vitrectomy for Rhegmatogenous Retinal Detachment: An Ultrasound Biomicroscopy Study - Zhao, Hongmei; Yu, Jian; Zong, Yuan; Jiang, Chunhui; Zhu, Haohao; Xu, Gezhi (Frontiers in Medicine, 2022)
Purpose: To investigate the characteristics of silicone oil (SO) emulsification after vitrectomy for rhegmatogenous retinal detachment (RRD) and possible correlations with clinical factors. Methods: Patients who underwent primary pars plana vitrectomy with SO injection for RRD followed by SO removal at the Eye and ENT Hospital of Fudan University between January 2016 and January 2020 were included. Ultrasound biomicroscopy (UBM) images of the anterior segment were taken before SO removal. Eight signs of SO emulsification in the UBM images were graded as 1 (present) or 0 (not present) and the grades for all signs in each eye were summed. Correlations between SO emulsification grade and clinical factors were determined. Results: A total of 118 patients (118 eyes) were enrolled in this study. Emulsified SO particles were found in all 118 eyes (100%). The eight signs were more frequently detected in the superior part of the eye. The mean total SO emulsification grade was 19.99 ± 12.98 (range: 1–36). Younger age and male (both P < 0.05) were associated with higher total SO emulsification grade. Patients with intraocular pressure (IOP) > 21 mmHg or the use of antiglaucoma medications at the time of SO removal had a higher total SO emulsification grade, were younger, and were more frequently male (all P < 0.05) than patients without ocular hypertension. Conclusions: UBM could play an important role in the diagnosis and grading of SO emulsification. Younger patients and males are more prone to SO emulsification, which may lead to elevated IOP.